2013
DOI: 10.1371/journal.pone.0074508
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Recombination and Conservation of Varroa destructor Virus-1 and Deformed Wing Virus in Field Collected Honey Bees (Apis mellifera)

Abstract: We sequenced small (s) RNAs from field collected honeybees (Apis mellifera) and bumblebees ( Bombus pascuorum ) using the Illumina technology. The sRNA reads were assembled and resulting contigs were used to search for virus homologues in GenBank. Matches with Varroa destructor virus-1 (VDV1) and Deformed wing virus (DWV) genomic sequences were obtained for A. mellifera but not B . pascuorum . Further analyses suggested that the prevalent virus population was composed of VDV-1 and a chimera of 5’-DWV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 80 publications
3
35
1
Order By: Relevance
“…We found no evidence of previously reported recombination within the N‐terminal region of the helicase gene (Dalmon et al ). Instead, we found limited evidence of recombination within the rdrp and lp genes, similar to reports from the UK (Moore et al ; Wang et al ). While these data cannot systematically address the question of genome‐wide recombination, our results give little evidence for an important role of recombination in the current spread of DWV.…”
Section: Discussionsupporting
confidence: 90%
“…We found no evidence of previously reported recombination within the N‐terminal region of the helicase gene (Dalmon et al ). Instead, we found limited evidence of recombination within the rdrp and lp genes, similar to reports from the UK (Moore et al ; Wang et al ). While these data cannot systematically address the question of genome‐wide recombination, our results give little evidence for an important role of recombination in the current spread of DWV.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, we sought to investigate if high levels of DWV in VH honeybees was associated with the limited accumulation of virus-derived siRNA, implying the virus may express an siRNA suppressor as, for example, demonstrated in Alphavirus infection of mosquitos [66]. Although DWV- and VDV-1 specific siRNAs were recently detected in adult honeybees [67], [68], these studies could not show if RNAi is involved in suppression of the virus, because viral genomic RNA levels were not quantified. Analysis of siRNAs in the honeybees of the frame transfer experiment showed that the predominant DWV- and VDV-1-specific siRNAs were 22 nt in length with genome sense strand-specific siRNAs present at a 3–4 fold excess over antisense.…”
Section: Discussionmentioning
confidence: 99%
“…Although prohibitive for high throughput diagnostics, the costs of NGS in the context of viral diversity research are often offset by the vast volumes of useful data that can be generated on viral population dynamics, co-infections, mutation frequencies and genetic recombination [22][24].…”
Section: Introductionmentioning
confidence: 99%